ATP‐binding cassette (ABC) transporters in cancer: A review of recent updates. Issue 3 (13th August 2021) - Wang, Jing‐Quan; Wu, Zhuo‐Xun; Yang, Yuqi; Teng, Qiu‐Xu; Li, Yi‐Dong; Lei, Zi‐Ning; Jani, Khushboo A; Kaushal, Neeraj; Chen, Zhe‐Sheng
Abstract: The ATP‐binding cassette (ABC) transporter superfamily is one of the largest membrane protein families existing in wide spectrum of organisms from prokaryotes to human. ABC transporters are also known as efflux pumps because they mediate the cross‐membrane transportation of various endo‐ and xenobiotic molecules energized by ATP hydrolysis. Therefore, ABC transporters have been considered closely to multidrug resistance (MDR) in cancer, where the efflux of structurally distinct chemotherapeutic drugs causes reduced itherapeutic efficacy. Besides, ABC transporters also play other critical biological roles in cancer such as signal transduction. During the past decades, extensive efforts have been made in understanding the structure‐function relationship, transportation profile of ABC transporters, as well as the possibility to overcome MDR via targeting these transporters. In this review, we discuss the most recent knowledge regarding ABC transporters and cancer drug resistance in order to provide insights for the development of more effective therapies.